Low Friction Coefficient of Phyllosilicate Fault Gouges and the Effect of Humidity: Insights From a New Microphysical Model. Issue 6 (11th June 2020) - den Hartog, S. A. M.; Faulkner, D. R.; Spiers, C. J.
Abstract: Fault slip is often localized in phyllosilicate‐rich fault gouges in a manner consistent with the relatively low friction coefficients measured for dry and especially wet phyllosilicates in laboratory experiments. However, the microphysics controlling these low friction coefficients remains unclear. Here, we propose a microphysical model, inspired by microstructural observations, for the prediction of the absolute value of the friction coefficient of pure dry and wet phyllosilicates. Experimentally produced phyllosilicate gouges suggest that shearing is controlled by sliding along (001) grain/platelet interfaces operating in series with removal of overlapping grain edge barriers by basal cleavage. We derive a model incorporating a subcritical crack propagation equation for the latter, constrained by subcritical crack growth data for muscovite. Model predictions for muscovite show similar trends regarding the effects of humidity and slip velocity on friction coefficient as do experiments at room temperature. The absolute value predicted for the friction coefficient is difficult to compare with experimental values, as it critically depends on atomic scale (001) sliding resistance, which is poorly constrained by available experimental data. Further discrepancies with experimental data can be explained by effects of varying grain size, grain aspect ratio, and porosity on the friction coefficient. While numerous qualitative explanations have been proposed previously for the low friction coefficient exhibited by phyllosilicates, especially in the presence of water, our study provides a new step toward a quantitative, physically based model. Key Points: We develop a cleavage‐based model for 2:1 phyllosilicate (muscovite) friction The model predicts realistic trends in friction coefficient with humidity and velocity Absolute friction coefficient depends on poorly constrained atomic scale shear resistance highlighting the need for additional experiments